The illusions of postmodernism - Eagleton, Terry (Blackwell Publishers, 1997)
In this brilliant critique, Terry Eagleton explores the origins and emergence of postmodernism, revealing its ambivalences and contradictions. Above all he speaks to a particular kind of student, or consumer, of popular "brands" of postmodern thought.